Firm productivity: The Role of Competition and of the Initial Firm Efficiency. Evidence from the Czech Republic - Lisbeth la Cour; Delia Ionascu (Copenhagen Business School (CBS), Department of Economics, 2007)
It has been argued that the effect of competition on a company's incentive to innovate and to reduce managerial slack depends on the initial level of efficiency. For example, while firms close to the technology frontier invest more in innovation if competition increases, backward firms reduce innovation. On a panel data of Czech companies, for the years 1993-2005, we empirically assess the impact of increased competition on firm productivity and the importance of the initial firm efficiency level. We depart from the empirical literature on emerging markets by taking into account both domestic and foreign competition. In line with the theory, our results show that there is an inverted U-relationship between domestic competition and firm productivity. Our results also confirm that trade liberalization has a positive impact on productivity. However, the effect is less significant if domestic competition is not taken into account. In addition, we find that both domestic and foreign competition have an effect on productivity in companies close to the technology frontier but not in backward companies.
hdl:10398/7653
Keywords: G10; 330